ANTESEDEN KEPERCAYAAN DAN SIKAP SERTA PENGARUHNYA TERHADAP ONLINE REPURCHASE INTENTION - Rastini, Ni Made; Nurcaya, I Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
The purpose of this study is to analyze the effect of trust and attitude on online repurchase intention on several online sites, such as Shopee, Lazada and other sites. The population in this study are people in Denpasar City and Badung Regency who have shopped online at sites such as Lazada, Shopee and other similar sites. The sample size used was 200 respondents, which were taken using the purposive sampling method. The analysis was carried out with Multiple Linear Regression analysis. The results of this study show that consumer trust and attitudes have a positive and significant effect on online repurchase intention. The variables of e-commerce knowledge, perceived reputation, and perceivde technology positively and significantly affect consumer confidence in online shopping sites, while the perceived risk variable has a negative effect on consumer confidence in online shopping sites. The results of this study are expected to be a study for marketers who have used online sites and those who have not used them so that they can formulate the right strategy to grow the interest of people who have never shopped online or maintain consumer loyalty so that the online shopping site is able to compete in the industry